Evidence for widespread hydrated minerals on asteroid (101955) Bennu - Hamilton, VE; Simon, AA; Christensen, PR; Reuter, DC; Clark, BE; Barucci, MA; Bowles, NE; Boynton, WV; Brucato, JR; Cloutis, EA; Jr, CHC; Hannah, KLD; et al. (Springer Nature, 2019)
Early spectral data from the Origins, Spectral Interpretation, Resource Identification, and Security-Regolith Explorer (OSIRIS-REx) mission reveal evidence for abundant hydrated minerals on the surface of near-Earth asteroid (101955) Bennu in the form of a near-infrared absorption near 2.7 µm and thermal infrared spectral features that are most similar to those of aqueously altered CM-type carbonaceous chondrites. We observe these spectral features across the surface of Bennu, and there is no evidence of substantial rotational variability at the spatial scales of tens to hundreds of metres observed to date. In the visible and near-infrared (0.4 to 2.4 µm) Bennu’s spectrum appears featureless and with a blue (negative) slope, confirming previous ground-based observations. Bennu may represent a class of objects that could have brought volatiles and organic chemistry to Earth.